How does cognitive control reduce anger and aggression? the role of conflict monitoring and forgiveness processes. [article]. - Wilkowski, Benjamin M.
It is well-established that superior cognitve control abilities are associated with lower levels of anger and aggression, However, the precise emotion regulation operations underlying this relationship have been underspecified and under explored in previous research. Drawing on neuro-psychological models of cognitive control, the authors propose that limited capacity resources can be recruited within a hostile situation to promote a process of forgiveness. The results of 2 studies supported this proposal. Across studies,individual differences in hostility-primed cognitive control were assessed implicitly. In study 1, hostility-primed cognitive control predicted less aggressive behavior in response to a laboratory provocation. Moreover, forgiveness mediated these effects . In study 2, hostility-primed cognitive control predicted forgiveness of provocations in participants' daily lives and subsequent reductions in anger. In sum, the results contribute to a systematic understanding of how cognitive control leads to lower levels of anger and aggression.
Keywords: Anger; Aggression; Cognitive control; Forgiveness; Emotion regulation